Normative Legal Review on the Implementation of the Main Thoughts of the DPRA in 2023 - Syahriga, Razik; Suganda, Delfi; Fithria, Nurul (Jurnal EL-QANUNIY: Jurnal Ilmu-Ilmu Kesyariahan dan Pranata Sosial, 2025)
Regulation of the Minister of Home Affairs Number 86 of 2017 was ratified in 2017. The researcher is particularly interested in Article 178 of this regulation, which discusses the review of main ideas. The study examines whether the established rules are appropriate and whether their implementation is effective and efficient. The first issue the researcher seeks to investigate is the mechanism for implementing the Pokir (Main Thoughts) of the DPRD Banda Aceh City, as well as the effectiveness of these rules in promoting regional development in the Syiah Kuala District, Banda Aceh City. In writing this article, the author employs the Normative Juridical approach. This methodology in legal research focuses on analyzing applicable laws and regulations about the legal issues being studied, ultimately leading to problem resolution. The findings of this research indicate that the rules formulated by the legislative institution are appropriate, as they provide clear guidelines for implementing policies based on community aspirations. Furthermore, their implementation has been efficient and well-executed, demonstrating harmony between regulation and field application. This synergy between local governments and legislative institutions ensures that the main ideas generated genuinely contribute to planning that is more responsive to community needs. Thus, this regulation plays a significant role in fostering a more participatory and welfare-oriented regional development process.